Clustering for global market access in Bangladesh: Endline survey - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The "Clustering for Global Market Access Survey" was conducted to assess the impacts of shrimp farm clustering interventions implemented by the Department of Fisheries (DoF), the Bangladesh Shrimp and Fish Foundation (BSFF), and a private sector actor. The survey was carried out in two rounds: a baseline in 2023 and an endline in 2024, to evaluate the effectiveness of these interventions. The data presented here are from the endline survey conducted between May 7 and May 31, 2024. Data were collected at the household, cluster, and community levels using a two-stage simple random sampling design and analyzed through a difference-in-differences approach. The household datasets include 1,222 shrimp farms across three districts in southern Bangladesh—Bagerhat, Khulna, and Satkhira. Among these, 622 are cluster farmers, and 600 are non-cluster comparison farmers situated in either the same or adjacent villages to cluster farmers. The data encompass cluster participation, pond characteristics, inputs received from cluster operators, stocking and harvesting, feed and non-feed input use, sales revenue, integrated farming, labor use, credit access, dietary diversity, and food security. The cluster datasets cover 68 shrimp farm clusters, providing insights into cluster composition and training delivered to cluster members. The community datasets provide contextual information on the 136 villages where both cluster and non-cluster farmers reside.